Carbon Accounting and Climate Risk Reporting: A Comprehensive Bibliometric Review - Abduh, Arridho; Hamzah, Muhammad Luthfi; Rusilawati, Ermina; Abdullah, Siti Intan Nurdiana Wong (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The increasing urgency of climate change mitigation has significantly elevated the importance of carbon accounting and climate risk reporting in both academic research and corporate practice. This study presents a comprehensive bibliometric review of scholarly publications on carbon accounting and climate risk reporting to map the intellectual structure, thematic evolution, and emerging research trends in the field. Using data extracted from the Scopus database, this review analyzes publications over the period 2000–2024. Bibliometric techniques, including performance analysis and science mapping (co-authorship, co-citation, and keyword co-occurrence analysis), are employed to identify influential authors, journals, institutions, and countries, as well as dominant and emerging research themes. The findings reveal a substantial growth in publications after the Paris Agreement (2015), reflecting increased global attention to climate-related financial disclosure, carbon assurance, ESG reporting, and sustainability governance. The intellectual structure of the field is primarily clustered around four major themes: (1) carbon disclosure and reporting quality, (2) assurance and verification mechanisms, (3) carbon management and performance measurement, and (4) climate risk, financial stability, and regulatory frameworks. Recent studies increasingly integrate climate risk reporting with financial performance, investor perception, and sustainable finance. This review contributes by providing a structured synthesis of the literature, highlighting research gaps, and proposing a future research agenda, particularly in relation to mandatory disclosure regimes, digitalization in carbon accounting, and the harmonization of global reporting standards. The results offer valuable insights for academics, policymakers, regulators, and practitioners seeking to enhance transparency, accountability, and decision-usefulness in climate-related financial reporting.